Loss of Carotenoid Plumage Coloration Is Associated With Loss of Choice for Coloration in Domestic Canaries - Koch, Rebecca E.; Hill, Geoffrey E. (Frontiers in Ecology and Evolution, 2019)
Understanding the evolution of mating display traits and preferences for them is a major aim of behavioral and evolutionary ecology. However, isolating the specific traits used as mate choice criteria and the possible genetic underpinnings of both trait and preference has proven difficult, particularly in natural systems offering little experimental control over key variables. In this study, we used discrete color morphs of otherwise phenotypically identical domestic canaries (Serinus canaria) in a mate choice apparatus to test whether breeding-condition female canaries show preference for males of varying color phenotypes (yellow, white, red, or wild-type green), using spatial association as a proxy for choice. We also used synthesized vocal recordings to examine whether females in our population exhibited mate choice for song characteristics, as has been demonstrated in this species. Contrary to previous study, we found that neither white nor yellow females in our colony showed any preference for males associated with songs of differing quality, and yellow females also did not prefer supernormal red or wild-type green males over yellow males. However, yellow—but not white—females demonstrated a preference to associate with yellow males over white males. We hypothesize that preference for brightly colored mates is ancestral in domestic canaries, but that strong artificial selection for white females to reproduce successfully with white males has eliminated the preference for color (along with color itself) in the white canaries.